ETIKA MORAL PENDIDIKAN DALAM MEMBENTUK KARAKTER PESERTA DIDIK - Ismira; Fenri Naldi; Elmasi Tri Oktaviani; Salsabila; Emi Sofia; Dutika Handayani (STKIP Subang, 2025)
Moral ethics in education serve as a fundamental pillar in shaping learning quality and fostering students’ character development. Teachers are not merely transmitters of knowledge but also moral role models who embody values such as honesty, responsibility, fairness, and respect for human dignity. This article provides a comprehensive analysis of the meaning of moral ethics in education, the urgency of moral ethics for teachers, strategies for developing ethical competence, the role of culture in strengthening moral values, challenges in ethical implementation, and approaches for integrating ethical practices into classroom learning. This study employs a literature review method to analyze theoretical perspectives from various relevant sources. The findings reveal that teachers’ moral ethics significantly influence classroom climate, student motivation, teacher professionalism, and character formation. Effective implementation of moral ethics requires professional awareness, institutional support, cultural reinforcement, and the integration of ethical values into all learning activities. Strong moral ethics not only create a safe, humanistic, and character-rich learning environment but also strengthen the position of teachers as moral and social agents within society.